Perubahan Panjang Lokalisasi dan Kerapatan Keadaan Elektron pada Molekul DNA Poli(dA)-Poli(dT) Karena Medan Magnet - Efta Yudiarsah; Andi Muhammad Risqi (Lambung Mangkurat University Press, 2018)
The localization length and the Density Of State (DOS) of electron in a Poly(dA)-Poly(dT) DNA molecule at two temperatures have been calculated for several values of magnetic field. The calculation are carried out on a DNA molecule model that consists of adenine (A) and Thymine (T) nucleobases and sugar-phosphate backbone. The DNA molecule is modeled in tight binding Hamiltonian approachwith semi empirical Slater-Koster theory and Peierls phase factor for introducing the effect of temperature and magnetic field, respectively. In the model, electron is allowed to move between nucleobase sites, backbode sites, and between backbone site and nucleobase site. The localization length is obtained from the smallest Lyapunov exponent which is calculated using transfer matrix method along with Gram-Schmidtorthonormalization procedure. The DOS is calculated using Green’s function methodby taking into account the presence of metallic electrode at both ends of the DNA molecule. The localization length and the DOS change as a result of the change in electron wave phase due to magnetic field. The change is observed at both temperature used in the study, but the change at lower temperature is larger than the one at higher temperature. Thermally agitated vibrational twisting motion perturbs electron motion in the DNA molecule such that the influence of magnetic field on the localization length and the DOS of electron at higher temperature becomes smaller.